Economical and ecological renewable solution based heating systems for residential building - Nichita Teodora-Mădălina; Girip Alina Viorica; Ilie Anica (E3S Web of Conferences)
This paper is an analysis which provides an objective perspective on the performance of different heating sources to facilitate informed decisions regarding investments in thermal energy production equipment that have a low impact on the environment. The aim of the study is to investigate different possibilities to reduce the power consumption and environmental impact taking account annual electricity consumption building for the central-western location in Romania. This paper presented the technical-cost benefit and environmental impact analysis of three alternative heating systems versus conventional systems with natural gas boiler. The obtained results show the higher cost is for ground-to-water heat pump solution and for pellet boiler the price initial investment is higher than that of a gas boiler with 2.15% but is like that of an air-to-water or ground-to-water heat pump. The total operating cost for pellet boiler, air-to-water heat pump and ground-to-water heat pump is higher than natural gas boiler with 65%, 23%, respectively 10%. The amount of CO2 emitted into the atmosphere decreases significantly with solutions air-to-water heat pump and ground-to-water heat pump, with the minimum value of 2502 kg CO2 obtained for the last.